Multiplex Therapeutic Drug Monitoring by Isotope-dilution HPLC-MS/MS of Antibiotics in Critical Illnesses - Schuster, Carina (J Vis Exp, 2018)
There is an ever-increasing demand for the therapeutic drug monitoring of antibiotics in many clinical facilities, particularly with regard to the implementation of hospital antibiotic stewardship programs. In the current work, we present a multiplex high-performance liquid chromatography-tandem mass spectrometry (HPCL-MS/MS) protocol for the quantification of cefepime, meropenem, ciprofloxacin, moxifloxacin, linezolid, and piperacillin, commonly used antibiotics in intensive care units. The method was previously comprehensively validated according to the guideline of the European Medicines Agency. After a rapid sample cleanup, the analytes are separated on a C8 reverse-phase HPLC column within 4 minutes and quantified with the corresponding stable isotope-labeled internal standards in electrospray ionization (ESI+) mass spectrometry in multiple reaction time monitoring (MRM). The presented method uses a simple instrumentation setting with uniform chromatographic conditions, allowing for the daily and robust antibiotic therapeutic drug monitoring in clinical laboratories. The calibration curve spans the pharmacokinetic concentration range, thereby including antibiotic amounts close to the minimal inhibitory concentration (MIC) of susceptible bacteria and peak concentrations (C(max)) that are obtained with bolus administration regimens. Without the necessity of the serum dilution before the sample cleanup, the area under the curve for an administered antibiotic can be obtained through multiple measurements.